Marino's the ICU book - Marino, Paul L. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"A fundamental sourcebook for the care of critically ill patients. This edition continues the original intent to provide a generic textbook that presents fundamental concepts and patient care practices that can be used in any adult intensive care unit, regardless of the specialty focus of the unit."--Provided by publisher